Tailored transition metal-doped nickel phosphide nanoparticles for the electrochemical oxygen evolution reaction (OER) - Man, H; Tsang, C; Li, M; Mo, J; Huang, B; Lee, L; Leung, Y; Wong, K; Tsang, S (Royal Society of Chemistry, 2018)
Foreign transition metals are doped into the hexagonal nickel phosphide structure through a simple and facile bottom-up wet-chemical synthesis process via stabilization with oleylamine, trioctylphosphine (TOP), and trioctylphosphine oxide (TOPO): the as-prepared transition metal-doped nickel phosphide nanoparticles show a high level of doping but create no significant distortion of the crystal structure and morphology against pristine nickel phosphide nanoparticles, which exhibit excellent activity in the electrochemical oxygen evolution reaction (OER), having overpotential as small as 330 mV at 20 mA cm−2 with a low Tafel slope value of 39 mV dec−1.